Near-infrared photocontrolled therapeutic release via upconversion nanocomposites - Wang, Zhimin (2022)
Photocontrolled therapeutic release holds great promise due to its versatile manipulability, superb spatiotemporal precision and minimal tissue invasiveness in biomedical purposes. However, most of light-responsive platforms thus far have relied on UV or visible light which substantially limit the potential applicability in living animals. In recent decades, near-infrared (NIR) light-mediated theranostic upconversion nanocomposites (UCNCs) that integrate conventional UV/Vis-sensitive materials and classic lanthanide-doped upconversion nanoparticles (UCNPs) have significantly promoted the development of deep-tissue photoreleasable therapeutics in vivo. Herein, we seek to review current NIR upconversion triggered photorelease techniques and their diverse applications in the biological regulation, as well as diseases therapy. In addition, the future perspectives and challenges for advancing UCNCs based NIR photoreleasable nanotherapeutics into clinical translations are proposed.